Specificity of Esthetic Experience for Artworks: An fMRI Study - Di Dio, Cinzia; Canessa, Nicola; Cappa, Stefano F.; Rizzolatti, Giacomo (Frontiers in Human Neuroscience, 2011)
In a previous study aimed at investigating the neural correlates of aesthetic experience in the beholder we found that observation of canonical sculptures, relative to sculptures whose proportions had been modified, produced the activation of a specific brain network. This network included various cortical areas and, most interestingly, the right anterior insula. We interpreted this latter activation as the neural signature underpinning emotion-related responses during aesthetic experience. In the present fMRI study, we investigated whether aesthetic experience for Classical sculptures has a quality of its own, distinct from that underpinning observation of real human bodies. Sculpture images and pictures of young athletes, matched to sculptures for body postures and proportions, were used as stimuli. Participants were students naïve to art criticism. Results showed a similar activation pattern for the two stimulus-categories. Direct comparisons between stimulus-categories highlighted, however, some relevant differences. Observation of sculptures, relative to real human body images, determined a greater activation of some visual areas, including fusiform gyrus, plus the right anterior insula. The opposite contrast showed a stronger activation of the superior temporal sulcus. Moreover, canonical proportion in sculpture, but not in human body images, produced a stronger activation of the right anterior insula with respect to proportion-modified images. These data show that, during observation of sculpture images, attention is more attracted by specific visual aspects of the stimulus, whereas observation of real human body images activates areas encoding biological movement. Most interestingly, sculptures elicited activations in right anterior insula, which we suggested to be crucial in hallmarking emotional responses during aesthetic experience. This pattern was poorly expressed during observation of human bodies, suggesting poverty of true aesthetic experience.